Antarctic temperature studies utilizing HRIR data from Nimbus I - Kerman, William Oscar, Jr.; Frame, Don Dale (Monterey, California. U.S. Naval Postgraduate School, 1966)
Eighty nine orbits of Nimbus I High Resolution Infrared (HR IR) data (August 28 - September 2 2, 1964) were analyzed and compared to data from the reporting stations on the continent of Antarctica. Out of 281 station reports containing all types of weather typical of the Antarctic, it was found that the surface temperature of stations reporting cloudless conditions correlated best with the HR IR temperatures interpreted from the HR IR film. This paper includes a discussion of the methods used and the difficulties encountered in extracting usable data from the low contrast HR IR pictures over a homogeneous ice and snow covered area. Approved for public release; distribution is unlimited. Lieutenant, United States Navy Lieutenant, United States Navy http://archive.org/details/antarctictempera109459437